الحسن والقبح بين مقصد القرآن ومقصد المتكلمين" المعتزلة والأشاعرة" - بن سعيد، لطيفة (جامعة الأمير عبد القادر للعلوم الإسلامية - كلية أصول الدين, 2016)
في ورقة البحث هذه سأحاول الإجابة عن التساؤل الذي طرحته حول الحسن والقبح بين مقصد القرآن ومقصد المتكلمين، عرفت بداية بمصطلحات الحسن والقبح والمقصد، ثم عرضت مسألة الحسن والقبح في القرآن الكريم من خلال استقصاء الآيات التي ورد فيها هذا الموضوع في مجالاته المختلفة؛ ما تعلق منها بالله تعالى وأفعاله، وما تركز حول أفعال المكلفين؛ أقوال وأعمال وأخلاق وآداب، حث فيها على الحسن، ونهى عن القبيح منها، والغاية المتوخاة من الأمر والنهي، ثم ثنيت بعرض مسائله عند المتكلين التي بحثوها في دراستهم لهذا الموضوع، والمنحى الذي سار فيه هؤلاء لتحقيق مقصدهم، لأختم البحث بخلاصة تجيب عن التساؤل المطروح في مقدمة هذا المقال.
The present study aims at shedding light on how the notions of ‘beauty and ugliness’ are actually used in the Holy Koran, and how they are interpreted by ‘mutakallimūn. First, the key terms of beauty, ugliness and intention are defined. Then, the two concepts under consideration (i.e. beauty and ugliness) are presented through a minutiuous of the Koranic verses where they are mentioned. They are discussed in relation to Allah the Almighty and his actions, to people’s deeds, to words, works, morals and ethics God urges to be nice and forbids to be ugly. Also, reference is made to the purposes lying behind such commandment and proscription. Furthermore, consistency with previous research is dealt with. As a conclusion at this article an answer to the problematic at the outset of this research work is provided.
Keywords: المقاصد القرآنية -- الفرق الاسلامية -- مذهب المعتزلة -- مذهب الأشاعرة -- العقيده الاسلامية